7 survival skills for a reengineered world - Yeomans, William N. (New York, N.Y. : Plume, 1998)
Offers advice on guiding one's own career and tells how to develop skills that increase one's value to present and future employers.
Originally published: New York : Dutton, 1996.
Includes bibliographical references (p. [326]-331) and index.
oif 26/03/15
Loan
Keywords: Vocational guidance; Interpersonal communication; Interpersonal relations; Self-management (Psychology); Human relations